Karakteristik Pluralitas Agama di Aceh - Abd Wahid (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Basically, different types of diversity in all its forms are not something that happen  because of a mistake of God. God is the One Almighty who may not do the slightest mistake.  Then, can the mistake be transferred to other than God, such as the nature and human  themselves? It is impossible to answer the question “yes.” Then another question we should  ask is not who is mistaken for the occurrence of this diversity, but what is the wisdom behind  the diversity itself. This article examines the understanding and the characteristic of the  plurality of religions in Aceh. It is very important to be explored because Aceh has a mandate  as a special area. The specificity includes the enactment of Islamic law and the implementation  of governance set out in the Law on Governing Aceh.